2018
DOI: 10.1002/cncr.31538
|View full text |Cite
|
Sign up to set email alerts
|

Cells, cytokines, chemokines, and cancer stress: A biobehavioral study of patients with chronic lymphocytic leukemia

Abstract: Novel biobehavioral data from patients with relapsed/refractory CLL demonstrate that stress is related to heightened levels of cellular, cytokine, and chemokine markers associated previously with progressive disease in CLL. The current results indicate that stress is related to immune and inflammatory processes that contribute to cancer cell proliferation and survival. These data provide a first look into these processes. Cancer 2018. © 2018 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 79 publications
(141 reference statements)
0
24
0
3
Order By: Relevance
“…IL-6 is a cytokine with a wide variety of functions and its expression is typically elevated as part of the immune response (19). The production of IL-6 is stimulated by foreign bodies, including bacteria, endotoxin and dust particles (20).…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 is a cytokine with a wide variety of functions and its expression is typically elevated as part of the immune response (19). The production of IL-6 is stimulated by foreign bodies, including bacteria, endotoxin and dust particles (20).…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant secretion of cytokines to tumor site is one of the features of CAFs. It is acknowledged that cytokines serve as mediators in shaping tumor microenvironment and facilitating tumor progression . Previous studies have reported that C‐X‐C motif chemokine ligand 12 (CXCL12), interferon‐γ (IFN‐γ), CXCL9/10/11 and IL6 promoted PD‐L1 expression in cancer cells .…”
Section: Introductionmentioning
confidence: 99%
“…It is acknowledged that cytokines serve as mediators in shaping tumor microenvironment and facilitating tumor progression. 9,10 Previous studies have reported that C-X-C motif chemokine ligand 12 (CXCL12), interferon-γ (IFN-γ), CXCL9/10/11 and IL6 promoted PD-L1 expression in cancer cells. [11][12][13][14] In this regard, we postulated that CAFs-derived cytokines might promote PD-L1 expression.…”
Section: Introductionmentioning
confidence: 99%
“…Kini et al in their study reflected the link between pathological angiogenesis and tumor clone in CLL, which revealed a significant rise in the density of microvessels in bone marrow biopsies of the patients, suffering from CLL, compared with control sections [45]. In addition, interleukins 10 and 6, produced by B-lymphocytes in excess of the norm, participate in the angiogenesis stimulation in CLL [46,47]. Meta-analysis demonstrated that interleukin-10 expression predicted the worst progression-free survival in patients with hematological malignancies [48].…”
Section: Relationship Between Pathological Angiogenesis and Vegf Levelmentioning
confidence: 98%